Analisis Kelayakan Harga Saham Melalui Analisis Fundamental Dan Tekhnikal Pasar Modal Syariah - NURCAHYO DARMAWAN, ARI; AMIR MAS'UD, ANUDIYAN (JOURNAL KOPERASI DAN MANAJEMEN, 2024)
The purpose of the research is to determine the stock price assessment in a company and also to see what the public buys the stock from it. However, in this case, one must analyze what is in the stock, such as fundamentals and technicals. Fundamentally in terms of stocks used are the IHSG and also its trading volume. Fundamental analysis itself determines stocks and also pays attention to calculating factors in competition in their business. Fundamental analysis is a security that is below or above the determining price. Meanwhile, technical analysis is a behavior that is depicted in a graph to determine the stock price and also to monitor the rise and fall of traders in stocks. In determining the stock price assessment, a company must be able to determine or find out in advance the value of the company, how to increase its market capital and see the stock value that tends to increase.